2008
DOI: 10.1074/jbc.m804069200
|View full text |Cite
|
Sign up to set email alerts
|

The Basis for Selective E1-E2 Interactions in the ISG15 Conjugation System

Abstract: E1 and E2 enzymes coordinate the first steps in conjugation of ubiquitin (Ub) and ubiquitin-like proteins (Ubls). ISG15 is an interferon-␣/␤-induced Ubl, and the E1 and E2 enzymes for ISG15 conjugation are Ube1L and UbcH8, respectively. UbcH7 is the most closely related E2 to UbcH8, yet it does not function in ISG15 conjugation in vivo, while both UbcH7 and UbcH8 have been reported to function in Ub conjugation. Kinetic analyses of wild-type and chimeric E2s were performed to determine the basis for preferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 38 publications
5
50
0
Order By: Relevance
“…Surprisingly, in our previous study [13], two highly homologous E2 enzymes, UbcH6 (UBE2E1) and UbcH8 (UBE2E2) were identified to show remarkable different E3 interaction patterns. The astonishing difference in the E3 (RING) interaction profiles of those two enzymes, despite their high similarity, is supported by biochemical and functional evidences that suggest a minor role for UbcH8 in ubiquitin-conjugation while UbcH6 is reported as a major ubiquitin-conjugating enzyme [17]. While UbcH6 was shown to interact with approximately 24 RING-finger domains, UbcH8 only contacts two RING E3s [13].…”
Section: Resultsmentioning
confidence: 94%
“…Surprisingly, in our previous study [13], two highly homologous E2 enzymes, UbcH6 (UBE2E1) and UbcH8 (UBE2E2) were identified to show remarkable different E3 interaction patterns. The astonishing difference in the E3 (RING) interaction profiles of those two enzymes, despite their high similarity, is supported by biochemical and functional evidences that suggest a minor role for UbcH8 in ubiquitin-conjugation while UbcH6 is reported as a major ubiquitin-conjugating enzyme [17]. While UbcH6 was shown to interact with approximately 24 RING-finger domains, UbcH8 only contacts two RING E3s [13].…”
Section: Resultsmentioning
confidence: 94%
“…The UbcH8 family of carrier proteins is closest in sequence to UbcH7 among the E2 families but is relatively specific for charging by UbE1L, the activating enzyme for the interferoninduced ISG15 ubiquitin-like protein, although it can be forced to function with Uba1 under nonphysiological conditions (54,55). Surprisingly, UbcH8 is nearly as efficient as UbcH7 in supporting E6AP-catalyzed chain formation at saturation, as judged by their similar k cat values; Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…3). By inhibiting ISG15 conjugation in A549 cells with the UbE1L and ISG15 siRNAs, the synthesis of the viral NS1A, HA, NP, and M1 proteins was partially rescued ( To establish that ISG15 conjugation rather than free ISG15 mediated the inhibition of viral protein synthesis, we used an siRNA that targeted UbcH8, the E2 enzyme in ISG15 conjugation (5,10,29). The UbcH8 siRNA effectively inhibited UbcH8 protein production and ISG15 conjugation (greater than 95% and 85%, respectively), whereas no effect on the accumulation of free ISG15 was detected ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the human enzymes that catalyze this conjugation, the UbE1L E1 enzyme, the UbcH8 E2 enzyme, and the Herc5 E3 enzyme, are also induced by IFN-␤ (4,10,26,27,29). Although it had been reported that UbcH8 functions in both ISG15 and ubiquitin conjugation (3,10,13,25,28,29), a recent study demonstrated that UbcH8 is unlikely to function in ubiquitin conjugation in vivo for two reasons: K m measurements revealed that the E1 ubiquitin-activating enzyme, unlike UbE1L, exhibits very low affinity for UbcH8, and UbcH8 is poorly, if not at all, expressed in the absence of IFN treatment, indicating that UbcH8 functions only during the IFN response (5). A large number of human proteins that are targets for ISG15 conjugation have been identified (22,26,30).…”
mentioning
confidence: 99%